Determinants of pediatrics emergency mortality at comprehensive specialized hospitals of South nation nationalities and people region, Ethiopia, 2022: unmatched case-control study - Hiwot Tsegaye; Alebachew Demelash; Dawit Aklilu; Bekahegn Girma (BMC, 2023)
Abstract Background Globally, child mortality is remaining high, especially in sub-Saharan African countries like Ethiopia. Mortality which happens within 24 hours of admission is preventable. However, in Ethiopia little is known regarding pediatric emergency mortality. Therefore, this study was aimed to identify determinants of pediatric emergency mortality at compressive specialized hospitals found in South Nation Nationalities and people region, Southern Ethiopia. Methods A facility-based unmatched case-control study was conducted on 344 children (115 cases and 229 controls) at comprehensive specialized hospitals of South Nation Nationalities and people region, Ethiopia. The data collection checklist was checked for its consistency. Data were entered and cleaned for missed values by using Epi Data3.1, then exported to Stata version 14.1 for analysis. Logistic regression was done to identify the significant determinants for pediatric emergency mortality. Finally, AORs at 95% CI and P-value < 0.05 were used to declare statistical significance. Result A total of 344 charts were reviewed, of which 333 (97%) (112 cases and 221 controls) charts fulfilled the inclusion criteria.. In multivariable analysis, delayed diagnosis and treatment [AOR = 2.088, 95% of CI (1.128, 3.864)], acute respiratory distress syndrome [AOR = 2.804, 95% of CI (1.487, 5.250)], dehydration [AOR = 3.323, 95% of CI (1.260, 8.761)], meningitis [AOR = 5.282, 95% of CI (2.707, 10.310)], sepsis [AOR = 4.224, 95% of CI (2.220, 8.040)], accidental injury [AOR = 3.603, 95% of CI (1.877, 6.916)] and duration of sign/symptoms [AOR = 5.481, 95% of CI (2.457, 12.230)] were significantly associated with pediatric emergency mortality. Conclusion In the current study, delayed diagnosis and treatment, acute respiratory distress syndrome, dehydration, sepsis, meningitis, accidental injury and duration of signs/symptoms were significantly associated with pediatric emergency mortality. Healthcare professionals should identify and treat patients early at an emergency department and provide attention to patients with the above diseases. Furthermore, quality care should be provided.